Study About an Assembly of Iron(Iii) Hexacyanoferrate(Ii) and α-fe2o3 as a Secondary Photocell: Part 1 Synthesis, Characterization and Photoelectrochemical Properties of Fto/Α-Fe2o3/Kfe[Fe(Cn)6]3 Electrode System - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier B.V., 2020)
This study addresses the synthesis and characterization of iron(III) hexacyanoferrate(II) (Prussian blue, PB) deposited on a semiconductor hematite electrode (α-Fe2O3). The formation of the Prussian blue/hematite interface was carried out by cyclic voltammetry. The modified electrode was morphologically characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), structurally by x-ray diffraction (XRD), and photoelectrochemically by cyclic voltammetry under polychromatic illumination. The structure of the electrode system shows a cauliflower type morphology, with the typical PB structure. The electrochemical characterization indicates an increase of the currents of the low- and high-spin iron systems of PB when the system is illuminated, indicating that photogenerated charge carriers are involved. © 2020 Elsevier B.V.